ALAT PENILAIAN PRODUKWEDDING PHOTOGRAPHY PADA MATA KULIAH PUBLIKASI MODE - Gery Ilhamsyah, - (2018)
Berdasarkanstudipendahuluan yang telahdilaksanakan, diperolehinformasibahwabelumadanyapedomanpenilaianuntukmenilaiprodukwedding photography pada Mata KuliahPublikasi Mode yang dipelajariolehmahasiswaPendidikan Tata BusanadenganPaketPilihanManajemanDesain Mode yang dilaksanakanpadatingkattiga semester enam. Hal tersebutmemotivasipenulisuntukmelakukansebuahpenelitiandanmengkajilebihdalammengenaialatpenilaianpembelajaran. Rubrikpenilaianmerupakansuatu format penilaian yang disusunsecarasistematis yang berisiaspek-aspek yang mempengaruhikualitassuatuprodukwedding photography.Tujuandaripenelitianiniadalahuntukmemformulasikanalatpenilaianprodukberuparubrikpenilaian yang dapatdigunakanuntukmenilaihasilkaryapara mahasiswadalammemotretmomen-momenpernikahanatau yang biasadiistilahkanwedding photography. Research and development atau yang biasadisingkat R&D adalahsebuahmetodepenelitian yang digunakandalampenelitianini. Hasildaritahapvalidasiterhadapalatpenilaianprodukwedding photography menunjukankategori "sangatlayak" denganpresentasekelayakansebesar 82,8% dariahlievaluasidansebesar 93,6% dariahlimateriwedding photography yang meliputienamaspek, yaituaspekpencahayaan, aspekkomposisi, aspekmomen, aspeklatarfoto, aspekekspresi, danaspek pose. Alatpenilaianprodukwedding photography yang telahdibuatdapatdijadikanstandardisasiatauacuandalammelakukanpenilaianterhadapkaryamahasiswaberupaprodukwedding photography. ;---Based on the preliminary study that has been carried out, information is obtained that there is no assessment guideline to assess wedding photography products in the Mode Publication Course studied by Fashion Design Education students with the Fashion Design Management Choice Package that is carried out at level three sixth semester. This motivates the writer to do a research and study more deeply about learning assessment tools. The assessment rubric is a systematic assessment format that contains aspects that affect the quality of a wedding photography product. The purpose of this study is to formulate a product assessment tool in the form of an assessment rubric that can be used to assess the work of students in photographing wedding moments or commonly termed wedding photography. Research and development or commonly abbreviated as R & D is a research method used in this study. The results of the validation phase of the wedding photography product assessment tool show the category "very feasible" with a percentage of feasibility of 82.8% of the evaluation experts and 93.6% of the material experts wedding photography covering six aspects, namely lighting aspects, aspects of composition, aspects of the moment, aspects of the background of the photo, aspects of expression, and aspects of the pose. The wedding photography product assessment tool that has been made can be used as a standardization or reference in assessing student work in the form of wedding photography products.